Enhancing SART Validity by Statistically Controlling Speed-Accuracy Trade-Offs - Seli, Paul; Jonker, Tanya R.; Cheyne, James A.; Smilek, Daniel (Frontiers in Psychology, 2013)
Numerous studies focused on elucidating the correlates, causes, and consequences of inattention/attention lapses employ the Sustained Attention to Response Task (SART), a GO-NOGO task with infrequent withholds. Although the SART has become popular among inattention researchers, recent work has demonstrated its susceptibility to speed-accuracy trade-offs (SATOs), rendering its assessment of inattention problematic. Here, we propose and illustrate methods to statistically control for the occurrence of SATOs during SART performance. The statistical solutions presented here can be used to correct standard SART error scores, including those of already-published data, thereby allowing researchers to re-examine existing data, and to more sensitively evaluate the validity of earlier conclusions.